2017
DOI: 10.4103/ijstd.ijstd_55_16
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of metabolic syndrome in HIV-infected individuals

Abstract: Background:Metabolic syndrome (MS) is a cluster of risk factors for cardiovascular disease and Type 2 diabetes mellitus.Objectives:The aim is to assess the prevalence of MS in HIV patients receiving highly active antiretroviral therapy (HAART) and to compare it with treatment naïve HIV patients.Methods:Cross-sectional study carried out in a teaching hospital in North India. A total of 116 HIV positive patients who were on HAART and those who were treatment naïve were included in the study. Adult Treatment Pane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Metabolic syndrome was common among ART-experienced adults in Zambia, with a prevalence of 26.3% (95% CI 23.9–29.1), and it appears to be associated with inflammatory markers, sociodemographic, anthropometric, clinical, and laboratory characteristics. Other investigators have also observed high prevalences of MetS in similar groups in Ethiopia, [ 21 ] Cameroon [ 22 ] India, [ 23 , 24 ] Thailand, [ 25 ] and Portugal. [ 26 ] However, those studies reported a range of prevalences which could be partly explained by differences in sociodemographics, MetS definitions, and ART regimens.…”
Section: Discussionmentioning
confidence: 86%
“…Metabolic syndrome was common among ART-experienced adults in Zambia, with a prevalence of 26.3% (95% CI 23.9–29.1), and it appears to be associated with inflammatory markers, sociodemographic, anthropometric, clinical, and laboratory characteristics. Other investigators have also observed high prevalences of MetS in similar groups in Ethiopia, [ 21 ] Cameroon [ 22 ] India, [ 23 , 24 ] Thailand, [ 25 ] and Portugal. [ 26 ] However, those studies reported a range of prevalences which could be partly explained by differences in sociodemographics, MetS definitions, and ART regimens.…”
Section: Discussionmentioning
confidence: 86%
“…MetS prevalence in PLWH is commonly evaluated by the Adult Treatment Panel III (ATP III) and International Diabetes Federation (IDF) criteria. Using these criteria, it was shown that the prevalence of MetS is comparable in PLWH versus HCs, but higher in PLWH under ART compared with ART-naïve PLWH [84,85]. Overall, patients with MetS were older, HIV-infected for a longer time, and presented with a higher body mass index (BMI).…”
Section: Non-aids Co-morbidities In Plwhmentioning
confidence: 99%
“…Significant associations were observed with type of ART and low CD4 cell counts. Theengh D.et al, Estrada V et al, and Drelichowska J. et al also showed higher metabolic and body fat abnormality in HIV-infected adults specially those who were taking ART and HIV-associated lipodystrophy was found to be associated with several host, disease, and drug factors [6][7][8]. While prevalence of lipoatrophy increased with the use of indinavir and stavudine (now out of use and banned in many countries), lipoaccumulation was associated with duration as well as type of ART specially protease inhibitors.…”
Section: Discussionmentioning
confidence: 94%